El teatro mapuche escrito en femenino - Gonzalo Toledo Albornoz (IdeAs)
The aim of this article is to analyze the playwriting and staging of the Mapuche in the contemporary Chilean theater. To this end, it is necessary to analyze the historical background that allows to visualize the representation of the Mapuche in the theater, where the Mapuche community may or may not be present in its realization. This article starts, specifically, from the premise that the representation of Mapuche women and men, as subordinate individuals, has gone hand in hand with women`s writing as the result of a social and aesthetic emancipation, which has displaced those peripheral representations of Mapuche people issues towards the core of the national theatre production.